The Effectiveness of Lavender Aromatherapy Oil and Candle to Reduce The Pain in The Active Phase of 1st Stage of Labor - Karningsih Karningsih; Jehanara Jehanara; Winancy Winancy; Fauziah Yulfitria (Asosiasi Pendidikan Kebidanan Indonesia (AIPKIND), 2022)
ABSTRACT Background: The period of labor often causes excessive anxiety in the mother due to the pain felt. It can affect the delivery process. Various non-pharmacologic methods have been developed to reduce labor pain. Purpose: This study aimed to assess the different in the effectiveness of lavender aromatherapy with oil and candles to be inhaled on reducing labor pain in the first stage of the active phase of labor. Methods: This was a quantitative study and a quasi-experimental design with a pretest-posttest design with a control group. The sampling technique used purposive sampling with a total sample of 60 respondents. Samples were taken randomly and divided into three groups (aromatherapy oil, aromatherapy candles, control). Labor pain was measured using a numeric rating scale in the first stage of labor before and after the intervention. The research analysis used the Anova test which was useful to determine the difference in the effectiveness of candles and aromatherapy oils in reducing labor pain. Results: Candles and lavender aromatherapy oil can reduce labor pain in the first stage of active phase of labor compared than control (p-value= 0.001). Lavender oil was found to be more effective in reducing pain compared to lavender aromatherapy candles, with the means score of labor pain after administration of lavender oil was 3.50 compared to lavender aromatherapy candles was 5.05. Conclusion: Lavender aromatherapy oil found to be more effective in reducing labor pain in the first stage of active phase compared to aromatherapy candles. Midwife could facilitate the administration of lavender aromatherapy to reduce pain during labor